Penerapan Prinsip Kerja sama Di Dalam Percakapan Antara Iqbaal D Ramadhan Dan Najwa Shihab: Kajian Pragmatik - Siti Hafifah (DIALEKTIKA: JURNAL BAHASA, SASTRA DAN BUDAYA, 2023)
Currently, there are many discussion broadcast programs discussing exciting and interesting topics both on YouTube and on television. An example of a discussion broadcast program is the Mata Najwa program which is broadcast on television and Youtube. These activities involve participants performing speech acts. Speech acts are individual psychological symptoms in language. A discussion broadcast on YouTube or on television will be watched by the community, and for that participants need to apply the principle of cooperation in communicating. The application of the principle of cooperation in communication will make communication smooth and directed. This study aims to describe the application of the principle of cooperation and its benefits in the discussion between Iqbaal D Ramadhan and Najwa Shihab at the Mata Najwa: One Special Purpose of Independence on August 20, 2020. The research method used is descriptive qualitative with listening technique. The resulting data is in the form of audio which is then transcribed into text. The data analysis stage uses a classification technique into several maxims, after which the data is presented and conclusions are made. The result of this research is to find 9 conversations that apply the cooperative principle and are classified into several maxims, namely the maxim of quantity, maxim of quality, the maxim of relation, and the maxim of manner. And the benefit of applying these maxims in a broadcast is to shorten the time in carrying out conversations and participants try to only say what is true and relevant. This research also discusses things that violate the principle of cooperation, includina g: the existence of implicatures and humor, as well as the influence of cultural and situational factors that can expand the topic of conversation.